PWE-194 Randomised study of RIGJ vs PEGJ in Patients at Risk of Aspiration Pneumonia. (4th June 2013) - Lewis, S; Latchford, A; Gruning, T
Abstract : Introduction: In patients at risk of aspiration pneumonia due to gastro-oesophageal reflux who require gastrojejunostomy feeding tubes, the tubes are placed either radiologically (RIGJ) or endoscopicaly (PEGJ). There is little published evidence to inform which is superior. Methods: Consecutive patients referred for long-term jejunal feeding because of high risk of aspiration pneumonia (proven GORD or pneumonia whilst being NG fed) were randomly allocated to have a RIGJ or PEGJ inserted. A Tc99m colloid study was done to determine the presence of gastro-oesophageal reflux and jejunal gastric reflux after feeding tube placement. We recorded pneumonia, death, feeding tube displacement, blockage and replacement to 90 days post placement. Results: 65 patients were randomised, 31 RIGJ and 34 PEGJ. Baseline characteristics including Barthell index were similar between groups. GORD was demonstrated by Tc99m tracer injected intragastrically in 52% but in no patient when injected jejunally. Jejunal feeding tube and clinical complications (number). Conclusion: There was little difference in clinical outcomes between RIGJ vs PEGJ tubes for feeding patients at high risk of pneumonia. However, RIGJ tubes were considerably less prone to blockage and displacement than PEGJ tubes. Tube blockage was a major cause of frustration for patients and resource use for health care services. Replacing enteral tubes in frail patients was distressing and a significant use of health care resource. Consideration should be given to placing RIGJ in preference to PEGJ tubes. Disclosure of Interest: None Declared.